DELINEATION OF BUILDING FOOTPRINTS FROM HIGH RESOLUTION SATELLITE STEREO IMAGERY USING IMAGE MATCHING AND A GIS DATABASE - G. R. Dini; K. Jacobsen; C. Heipke (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
In this paper, a workflow is proposed to delineate building footprints from high resolution satellite stereo images through integration of a Digital Surface Model (DSM), 3D edge matching technique and GIS building polygons. First, Digital Surface Models (DSM) and a normalised DSM are derived by traditional image matching. Three different removal masks are employed to reduce the effects of matching errors, roads and vegetation. We then compare all resulting blobs with the GIS 2D building layer. For blobs without a partner in the database, building outlines are extracted based on 3D edge matching. To do so, edges on epipolar images are first detected individually on each image using the Canny operator. After removing short edges and extracting straight lines, we find the best corresponding lines using various constraints. Finally, the topological relationship of the derived 3D edges is employed to reconstruct the shape of the building and the building footprints using a box-fitting approach. Our experiments on GeoEye-1 stereo images show promising results if buildings are large enough, have simple shape and show good contrast compared to the background.